(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
By considering an account of shame provided in Buddhist philosophy and psychology, this article seeks to understand the suffering of those who have been unjustly shamed by the dissemination of disinformation. It seeks to provide a framework that avoids the danger of possible iatrogenic damage when therapists deny that the shame such people feel is ’real’. Furthermore, this article explores some of the ways in which this Buddhist account might offer therapeutic techniques to help ameliorate the suffering of the unjustly shamed.